2012
DOI: 10.1016/j.tube.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low dose of Mycobacterium tuberculosis aerosol creates partial infection in mice

Abstract: SUMMARY A murine low-dose (LD) aerosol model is commonly used to test tuberculosis vaccines. Doses of 50-400 CFU (24-hour lung CFU) infect 100% of exposed mice. The LD model measures progression from infection to disease based on organ CFU at defined time points. To mimic natural exposure, we exposed mice to an ultra-low dose (ULD) aerosol. We estimated the presented dose by sampling the aerosol. Female C57BL/6 mice were exposed to Mycobacterium tuberculosis H37Rv aerosol at 1.0, 1.1, 1.6, 5.4, and 11 CFU pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 17 publications
2
62
0
1
Order By: Relevance
“…The in vivo mouse protection model that we tested used a "low-dose aerosol" infection method: delivering ∼100-200 viable bacilli per mouse on average to ensure that every animal was infected. Nonetheless, this low-dose challenge represents 2 logs more than the actual infectious dose: although the precise infectious dose of Mtb is not known, it is thought that most sufficiently infectious microdroplets will harbor just one bacillus (36,37). Furthermore, we showed that protection was enhanced in vitro when the Mtb surface was not disrupted by detergents (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…The in vivo mouse protection model that we tested used a "low-dose aerosol" infection method: delivering ∼100-200 viable bacilli per mouse on average to ensure that every animal was infected. Nonetheless, this low-dose challenge represents 2 logs more than the actual infectious dose: although the precise infectious dose of Mtb is not known, it is thought that most sufficiently infectious microdroplets will harbor just one bacillus (36,37). Furthermore, we showed that protection was enhanced in vitro when the Mtb surface was not disrupted by detergents (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Generally, the majority of these studies employed aerosol routes to deliver M. tuberculosis challenge doses that are as low as possible and yet still ensure uniform infection and disease outcome for all animals. Thus, infection doses in experimental animal studies tend to be significantly higher (50 to 3,000 CFU per animal, commonly 10 to 20 for guinea pigs and 100 for mice) than the relatively few bacilli thought to be transmitted during natural exposure (though the precise number has never been measured) (91,(121)(122)(123). In addition, the bacillus is prepared under laboratory conditions with a metabolic state and physical conditions (sputum versus broth culture) that likely differ from those in natural transmission settings (93).…”
Section: Lessons From Bcgmentioning
confidence: 99%
“…For example, commercial rabbits are relatively resistant to M. tuberculosis, requiring approximately 300 to 3,000 inhaled bacilli to produce 1 primary pulmonary lesion, and are therefore less well suited for low-dose infection models (89). Another constraint for small-animal studies utilizing aerosol infection chambers is the potential for partial infection of a group of animals, as has been recently described for aerosol chamber infection of mice at doses lower than 10 CFU per infected animal (122). Guinea pigs are very susceptible to M. tuberculosis, generating roughly 1 primary pulmonary lesion per inhaled bacillus, and thus low-dose challenges may be delivered via infection chambers.…”
Section: Lessons From Bcgmentioning
confidence: 99%
See 1 more Smart Citation
“…88 • To simplify the innate immunity scenario, we included in our model only Nitric Oxide (N), 89 which was considered as the sole effective weapon against infection growth followed a logistic curve with a fixed growth rate (α 1 ), whose value was taken from 97 published work (Vijay S, 2014;Gil W, 2009;Ray JCJ, 2008). During early stages of infection, 98 which naturally occur at a low dose (Saini D, 2012), bacilli are confined in the infected 99 macrophages. Our model described a population of cells that accounted for both infected and 100 uninfected macrophages.…”
mentioning
confidence: 99%